Application of Design Thinking Method in Educational Card Design "Sobat Saleh" - Novena Ulita (Journal of Social Science, 2023)
: In developmental psychology theory, students are late adolescents who need to have problem-solving skills (Sahrah, 2019). Itis necessary to be trained in order to become a capable, creative and independent person in accordance with the goals of Indonesian national education. However, in the learning process in the studio class, the DKV study program which has the purpose of learning to hone students' thinking skills, often has difficulty solving a problem. A study that has been conducted previously that it is known that aspects of methods in solving problems are still confusing for students (Ulita &; Hananto, 2022). The research outlines that some students are still not fully aware of how to apply the method in designing. Therefore, this journal will describe the form of application of design thinking methods in a case study of designing an educational card game "Sobat Saleh" that can help student design learning that provides an overview of the process of solving problems into a design idea. Starting from data collection, analytical techniques and thinking processes as well as the form of application of the design thinking design method. Thus, it can be observed more deeply the patterns carried out in efforts to apply the design thinking method so as to help students more easily have the ability to solve problems with the method. The ability of critical thinking and creative things in solving problems can support the design logic that is needed by a designer when doing a design.